2019
DOI: 10.1093/ije/dyz008
|View full text |Cite
|
Sign up to set email alerts
|

How urban characteristics affect vulnerability to heat and cold: a multi-country analysis

Abstract: Background The health burden associated with temperature is expected to increase due to a warming climate. Populations living in cities are likely to be particularly at risk, but the role of urban characteristics in modifying the direct effects of temperature on health is still unclear. In this contribution, we used a multi-country dataset to study effect modification of temperature–mortality relationships by a range of city-specific indicators. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
136
2
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 185 publications
(156 citation statements)
references
References 47 publications
11
136
2
7
Order By: Relevance
“…A number of studies have shown associations between increased cardiovascular mortality and both high and low ambient temperature. A recent study of 340 cities and metropolitan areas from 22 countries (9 of which were classified as developing economies) estimated that 0.54% (95% CI: 0.49-0.58%) and 6.05% (95% CI: 5.59-6.36%) of mortality in those cities were respectively attributable to heat and cold [95]. Among the relatively few studies conducted in LMICs, high and low temperatures were associated with increased cardiovascular risk in India [96], many cities across China [97,98], and multiple countries in Latin America and sub-Saharan Africa [99][100][101][102][103].…”
Section: Ambient Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have shown associations between increased cardiovascular mortality and both high and low ambient temperature. A recent study of 340 cities and metropolitan areas from 22 countries (9 of which were classified as developing economies) estimated that 0.54% (95% CI: 0.49-0.58%) and 6.05% (95% CI: 5.59-6.36%) of mortality in those cities were respectively attributable to heat and cold [95]. Among the relatively few studies conducted in LMICs, high and low temperatures were associated with increased cardiovascular risk in India [96], many cities across China [97,98], and multiple countries in Latin America and sub-Saharan Africa [99][100][101][102][103].…”
Section: Ambient Temperaturementioning
confidence: 99%
“…Studies in Europe found associations between excess winter deaths from CVD and poor housing conditions, including lack of central heating and poor insulation [108,109]. A recent evaluation of 340 cities observed that the effects of heat on mortality were higher in cities with greater inequality, worse air quality, fewer green spaces, and lower availability of health services [95].…”
Section: Ambient Temperaturementioning
confidence: 99%
“…Heat-related mortality is, presumably, one of the most comprehensively studied consequences of climate change (Sera et al 2019). More frequent and longer heat waves increase mortality and morbidity, as demonstrated, for example, by Cheng et al (2014) for China and Gomez-Acebo et al (2012) for the north of Spain.…”
mentioning
confidence: 99%
“…Example are city population density, Gross Domestic Product (GDP), Gini Index (a measure of income inequality), and fine particles (PM2.5), etc. [47]. Therefore, in order to apply the health-temperature model and dataset to the thermal comfort study, a systematic investigation should be performed first, which is beyond the scope of this paper and will be discussed in greater details in the future [101].…”
Section: Comparison Between Health-temperature and Thermal Comfort Tementioning
confidence: 99%